The Application of Accounting Information Systems at CV Fael Jaya in the City of Manado - Salim, Yuricha Fransis Aprilia; Lambey, Robert; Gerungai, Natalia (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to understand the implementation of the accounting information system for cash receipts and cash expenditures at CV. Fael Jaya in the City of Manado, particularly in the sales department of goods (construction materials) based on the fundamental elements of the accounting information system. Given that this company is a growing enterprise, managing cash receipts and expenditures is crucial to facilitate accuracy and speed in all financial transaction processes within the company. The type of research used is a case study, and data are obtained from interviews and documentation. The data analysis technique employed is qualitative descriptive, in which the researcher elaborates on the implementation of the accounting information system at CV. Fael Jaya and then compares it with relevant theories about the accounting information system. The research findings indicate that the implementation of the accounting information system for cash receipts and expenditures at CV. Fael Jaya in the City of Manado is not yet adequate. Observing the functions and documents related to the theories and what occurs at CV. Fael Jaya, not everything aligns.